Pluralisme dalam Pondok Modern Gontor Ponorogo: Kajian Kitab Bidayat al-Mujtahid - El-Yunusi, M. Yusron Maulana (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
Pluralist-oriented education in principle has been applied in the modern cottage education system. This education has been included in the formal curriculum system and everyday learning processes. With the existing system, modern Islamic boarding schools have the potential to develop pluralist-oriented education, and deserve to be a successful example of the implementation of pluralist education. Although there are still some aspects that need to be further developed and refined. Darussalam Gontor boarding school is the first modern boarding school in Indonesia. Characteristics of modern boarding schools trying to combine traditionality and modernity of education. Wetonan and sorogan teaching systems were replaced with a classical system (in-class teaching) that was tiered and the integrated curriculum was adopted with certain adjustments. The dichotomy of religion and general science is also eliminated.